PENGARUH ILMU, LITERASI KEUNGAN, DAN DISEMINASI PASAR MODAL TERHADAP MINAT MAHASISWA AKUNTANSI DALAM BERINVESTASI DI PASAR MODAL - Elsa Juliana Elsa; Sekar Mayangsari (Lembaga Penerbit Fakultas EKonomi dan Bisnis, 2022)
When conducting this research, the aim is to examine the effect of knowledge, financial literacy, and capital market socialization on the interest of accounting students to invest in the capital market. In conducting this study, the researcher used quantitative methods as the basis for his assessment, for this research population was shown to Accounting Students, Trisakti University, West Jakarta. The research sample obtained was 101 respondents. The results shown from this study indicate that Science, Financial Literacy, and Capital Market Dissemination have a positive effect on the interest of Accounting Students in investing in the Capital Market. in supporting the capital market and growing the interest of Accounting Students to invest in the Capital Market